2004
DOI: 10.1021/la048711o
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH, Ionic Strength, and Temperature on Self-Association and Interactions of Sodium Dodecyl Sulfate in the Absence and Presence of Chitosan

Abstract: Chitosan is a cationic biopolymer that has many potential applications in the food industry because of its unique nutritional and physicochemical properties. Many of these properties depend on its ability to interact with anionic surface-active molecules, such as surfactants, phospholipids, and bile acids. The purpose of this study was to examine the influence of pH (3 and 7), ionic strength (0-200 mM NaCl), and temperature (10-50 degrees C) on the interactions between a model anionic surfactant (sodium dodecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
115
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 16 publications
14
115
1
2
Order By: Relevance
“…Cs possesses a pKa of near 6.5, with a maximum of one charge per residue. 26 The apparent dissociation constant of ChS has been estimated to be from 4.4 to 4.5. 51 Therefore, to formulate an effective nanoparticle combining Cs and ChS, it is necessary to create an electrostatic interaction between Cs cations and ChS anions, in which the positively charged amino groups of Cs interact with the negatively charged sulfate groups of ChS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cs possesses a pKa of near 6.5, with a maximum of one charge per residue. 26 The apparent dissociation constant of ChS has been estimated to be from 4.4 to 4.5. 51 Therefore, to formulate an effective nanoparticle combining Cs and ChS, it is necessary to create an electrostatic interaction between Cs cations and ChS anions, in which the positively charged amino groups of Cs interact with the negatively charged sulfate groups of ChS.…”
Section: Discussionmentioning
confidence: 99%
“…25 Cs has an intrinsic pKa near 6.5 with a maximum of one positive charge per residue. 26 "ChS" is a glycosaminoglycan present in the extracellular matrix of cartilage that is used in the treatment of osteoarthritis and demonstrates an anti-inflammatory activity. [27][28][29] ChS is also a component of the dermal layer of the US Food and Drug Administration-approved skin substitute, 30 commonly used to enhance re-epithelialization without causing scarring.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the binding between chitosan and anionic surfactants in acidic conditions is irreversible, i.e. after rising to neutral pH, they remain bound (35). This minimizes the risk that chitosan 128 nonspecifically binds to other surfaces (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has an intrinsic pKa near 6.5, with a maximum net positive charge of one per residue (54) . Chondroitin sulfates are glycosaminoglycans that are present in the extracellular matrix of cartilage, and they are used for the treatment of osteoarthritis and for their anti-infl ammatory activity (55) .…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 99%